Light and Electron Microscopic Localization of Presenilin-1 in Primate Brain - Lah, James J. (J Neurosci, 1997)
Several genes have been implicated in the pathogenesis of early-onset familial Alzheimer’s disease. A majority of the autosomal dominant cases are linked to recently identified mutations in the presenilin-1 gene on chromosome 14. The native presenilin-1 protein in primates has not been well characterized, and its precise localization is unknown. We have studied the native presenilin-1 protein in monkey brain and peripheral tissues by using a monoclonal antibody specific for the N-terminal domain of human presenilin-1. Western blots detect polypeptide species of ∼49 and ∼32 kDa from COS-7 and PC12 cells transfected with full-length human presenilin-1 cDNA and from in vitro translations of the normal human presenilin-1 mRNA. A 32 kDa polypeptide is detected in monkey peripheral tissues, with the highest expression in testis and lung. In all brain regions the 32 kDa band is the predominant form of presenilin-1, and it is found in particulate subfractions. Light microscopic immunocytochemistry reveals presenilin-1 staining in all brain regions, with the strongest labeling in neurons and neuropil. In addition, weaker immunoreactivity is also present in glia and blood vessels. Neuronal staining shows significant variability, with particularly intense labeling of certain cell types, including large neocortical and hippocampal pyramidal neurons, magnocellular basal forebrain neurons, brainstem motoneurons, and some populations of interneurons. By electron microscopic immunocytochemistry, highly selective presenilin-1 staining is seen on the cytoplasmic surfaces of membranous organelles, which suggest localization to the endoplasmic reticulum–Golgi intermediate compartment, a subdomain of the endoplasmic reticulum, and some coated transport vesicles.